2018
DOI: 10.2991/j.jegh.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of Noncommunicable Diseases in Kenya: An Examination of the Time Trends and Contribution of the Changes in Diet and Physical Inactivity

Abstract: This study examined correlations of historical changes in diet and physical inactivity with the rise of noncommunicable diseases (NCDs) in Kenya. Historical data on diet, wage jobs by industry, urbanization, gross domestic product (GDP), and morbidity due to NCDs were extracted from Kenya Statistical Abstracts, Food and Agriculture Organization (FAOSTAT), and the World Bank online database. These data were plotted and correlations between these factors and the incidence of different NCDs over time were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 20 publications
2
43
0
Order By: Relevance
“…The inclusion of dishes in the list of FFQ food items may improve accuracy and precision of the collected data in two ways [3,22]. First, NCDs are linked to culture-specific cooking methods and ingredients [3,[30][31][32]. Second, in the FFQs in which dishes are not included people may not report invisible parts of a mixed dish because they are neither engaged in their cooking process nor can see the ingredients of different recipes.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of dishes in the list of FFQ food items may improve accuracy and precision of the collected data in two ways [3,22]. First, NCDs are linked to culture-specific cooking methods and ingredients [3,[30][31][32]. Second, in the FFQs in which dishes are not included people may not report invisible parts of a mixed dish because they are neither engaged in their cooking process nor can see the ingredients of different recipes.…”
Section: Discussionmentioning
confidence: 99%
“…The high burden of overweight and obesity in Kenya could be attributed to the rapid urbanisation, economic development, and the related unhealthy behaviours such as consumption of energy dense processed food and sedentary lifestyles [51]. As an ecological study in Kenya has showed, there is a positive association between the rise of NCDs including hypertension in Kenya and the increase in per capita gross domestic product, urbanisation, physical inactivity and consumption of high dense processed foods such as cooking oil and wheat [52]. Surprisingly, undernutrition independently contributed 14.1% of the observed inequality, which could reflect the high prevalence of hypertension (16.7%) among the 16% of our study population who were undernourished.…”
Section: Discussionmentioning
confidence: 99%
“…The high burden of overweight and obesity in Kenya could be attributed to the rapid urbanisation, economic development, and the related unhealthy behaviours such as consumption of energy dense processed food and sedentary lifestyles [51]. As an ecological study in Kenya has showed, there is a positive association between the rise of NCDs including hypertension in Kenya and the increase in per capita gross domestic product, urbanisation, physical inactivity and consumption of high dense processed foods such as cooking oil and wheat [52]. Surprisingly, undernutrition independently contributed 14.1% of the observed inequality, which could re ect the high prevalence of hypertension (16.7%) among the 16% of our study population who were undernourished.…”
Section: Discussionmentioning
confidence: 99%